(untitled) (Research, Society and Development, 2023)
Introduction: In recent years, a growing body of evidence has indicated the possible association between vitamin D and depression. Like depression, vitamin D deficiency is also a major public health problem. The aim of this study was to evaluate the relationship between vitamin D status and the occurrence of depression. Methodology: This refers to an integrative literature review with a qualitative approach to the efficacy of vitamin D supplementation in the adjuvant treatment of patients with depression. Based on all the steps taken, the guiding question was: "Is vitamin D supplementation beneficial as an adjuvant treatment in patients with depression? The descriptors "vitamin D", "depression" and "deficiency" were used to search the articles. Initially, 762 articles were found. After reading the titles and abstracts, 34 articles were considered to be read in full. In the end, we obtained a sample of 5 studies. Results and discussion: As observed by the studies, the use of vitamin D brings benefits to the patient who is in a state of deficiency of this nutrient, being effective in improving depressive scores and general health status. The normalization of vitamin D levels was also able to decrease the dose of antidepressant medication prescribed to patients, also reducing adverse effects and possibly unwanted reactions. Conclusion: Therefore, we conclude that vitamin D is beneficial in the adjuvant treatment of depression in patients with deficiency of this substance.